Catheter - associated urinary tract infection: process indicators for analysis of prevention practices in critical patients - Caroline Cury Ferreira; Fernanda Leticia Frates Cauduro (Universidade de Santa Cruz do Sul, 2017)
Background and objective: Urinary tract infections have a significant impact on the patient's clinical evolution. In this way, the objective of this study was to analyze, through two process indicators. The conformities and nonconformities related to the practices of control and prevention of urinary tract infection related to delayed bladder catheterization in sectors with critical patients. Methods: Documental, observational and cross-sectional research of quantitative approach, performed in an Intensive Care Center and an Emergency unit of a public hospital in Curitiba. The data collection and analysis were based on process indicators elaborated and validated by Fernandez (2006). The indicators are evaluated accordingly when values between 73 - 87 % and 75 - 85 %, respectively. Results: For Indicators 1 and 2, the overall compliance rate was 68.8 % and 29.5 %, respectively. When the items that subsided the numerator of both indicators were registered, the indication for use of the device was more satisfactory in the Emergency (80.6 %) and the adequate fixation presented nonconformity in the two sectors evaluated (67.5 % in the Center for Intensive Care and 96.8 % in Emergency).Conclusion: In general, the indicators revealed nonconformities with regard to the prevention practices for urinary tract infection related to delayed bladder catheterization and address the need for the implementation of guidance strategies for care teams and continuous monitoring of catheter use. KEYWORDS: Indicators. Quality indicators, Health care. Urinary Tract Infections. Catheters, Indwelling.